Equilíbrio de fases de soluções polidispersas de polímeros - Melo Junior, Afrânio José de (2016)
The thermodynamic description of macromolecular solutions is naturaly different from traditional approaches. In particular, molar mass distributions introduce significant qualitative and quantitative differences in the phase behaviour. Despite increasead efforts in the field, little is found in literature regarding how this effect can influence the behavior of chemical engineering processes. The present study proposes the use of thermodynamic modeling to describe polypropylene extraction in xylene, the well-known XS (xylene solubles) test. The XS experiment constitutes a usual procedure in many polymer laboratories, used to determine the percentage of xylene solubles in samples of polypropylene, which correspond to an approximate measure of the atactic and oligomeric chains. To describe the mixtures, the Flory-Huggins model was extended to handle multicomponent polydisperse systems. The model was implemented in MATLAB ® and although relatively simple, fitted experimental data accurately after estimation of the polymer-solvent interaction parameter, χij . This concluded that the interaction parameter is a function of the polymer average molar mass and not of the degree of tacticity. The model can be easily extended to alow for description of other polydisperse polymer solutions.